A comparative study of the haptic technique: French language learning through movies for higher secondary education - K G, Sugesh; R, Calaivanane (International Journal of Innovative Research and Scientific Studies, 2023)
Progress in education is now beyond traditional and orthodox teaching approaches. Utilization of technology in teaching seems to be a pipe dream. Each day passes with modern interpretations and innovations. Teaching resources and technological advancement result in the desired outputs. When textbooks fail to lure learners’ attention, integrating learning with enjoyable sources appears to be an appropriate method to achieve the most. This strategy has its pros and cons. Teaching through movies might be difficult but when done well, it has multiple benefits. Unlike books, movies allow learners to acquire knowledge visually. The movie Gandhi, for instance, permits learners to experience a replica of Mahatma Gandhi’s biography. Visual samples provide a greater understanding of the period and era besides the culture of the historic figure. Furthermore, unlike books, movies are not restrained in any way. As a result, this study investigates the analytical perception of the pedagogical use of movies in French lectures as the practice is not as advantageous to French students as it appears. Following the implementation of a movie module in two French classrooms, a questionnaire was administered to 35 participants of first and second year higher secondary education to obtain feedback for analyzing the effectiveness of language acquisition. According to the data, French learners have extremely positive attitudes towards the movie-based method and consider it engaging and beneficial for enhancing linguistic and social skills.